2019
DOI: 10.1073/pnas.1907495116
|View full text |Cite
|
Sign up to set email alerts
|

A relatively wide-bandgap and air-stable donor polymer for fabrication of efficient semitransparent and tandem organic photovoltaics

Abstract: Organic photovoltaics (OPVs) have attracted tremendous attention in the field of thin-film solar cells due to their wide range of applications, especially for semitransparent devices. Here, we synthesize a dithiaindacenone-thiophene-benzothiadiazole-thiophene alternating donor copolymer named poly{[2,7-(5,5-didecyl-5H-1,8-dithia-as-indacenone)]-alt-[5,5-(5′,6′-dioctyloxy-4′,7′-di-2-thienyl-2′,1′,3′-benzothiadiazole)]} (PDTIDTBT), which shows a relatively wide bandgap of 1.82 eV, good mobility, and high transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…In fact, our tandem device is comparable with the state‐of‐art polymers reported in the literature in terms of stability. For instance, in one the stable tandem device reported in the literature, [ 38 ] the device retained 97% of its initial PCE value in ambient condition, which is similar to our stability results. However, we also measured the operational stability of our tandem device under continuous illumination and compared with both single‐junction bottom (PV2000:PCBM) and top (PM6:Y6) cells.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, our tandem device is comparable with the state‐of‐art polymers reported in the literature in terms of stability. For instance, in one the stable tandem device reported in the literature, [ 38 ] the device retained 97% of its initial PCE value in ambient condition, which is similar to our stability results. However, we also measured the operational stability of our tandem device under continuous illumination and compared with both single‐junction bottom (PV2000:PCBM) and top (PM6:Y6) cells.…”
Section: Resultssupporting
confidence: 90%
“…Besides reducing the PV losses (in V OC , FF, and current match) in a tandem OSC, the device stability is also required to be considered for the commercialization purposes. [ 7,38 ] Most of the reports in the literature just considered the efficiency of the tandem device, and therefore, more efforts need to be devoted to the stability of OSC tandem devices. Basically, researchers improved the stability of an OSC device by synthesis of donors and acceptors with a stable molecular structure and deep highest occupied molecular orbital level, interface engineering, and using protection and AR layers.…”
Section: Introductionmentioning
confidence: 99%
“…The surface roughness of the perovskite film can induce surface recombination at HTL/perovskite interface, resulting in lower open circuit voltage ( V OC ). [ 44–46 ] The crystallinity of the perovskite films deposited on solution‐ and evaporation‐based PTAA was investigated by X‐ray diffraction (XRD) pattern, as shown in Figure S5, Supporting Information. As seen, the perovskite film on the evaporated PTAA film shows peaks with slightly higher intensity, indicating better quality of the perovskite in this sample.…”
Section: Figurementioning
confidence: 99%
“…28,29 On this respect, the device engineering has played a key role for example with the development of tandem devices, consisting of multiple layers of different materials which usually show complementary absorption, [30][31][32] but the tandem devices fabrication requires complicated and expensive manufacturing. [32][33][34][35][36][37] A promising alternative for combining the improved photoconversion of tandem devices with the simplicity of the typical manufacturing processes of OSCs, is the realization of three-component heterojunctions. In this regard, Honda et al reported an enhancement of the light-harvesting efficiency in P3HT:PCBM BHJ solar cells by employing nearinfrared phthalocyanine molecules as the third component of the active layer.…”
Section: Introductionmentioning
confidence: 99%